Effect of e-evaluation on work motivation among teachers during the movement control order in COVID-19: the mediating role of stress - Sulaiman, Tajularipin; Ibrahim, Amalina; Motevalli, Saeid; Wong, Kai Yan; Abdullah, Muhammad Nazrul Hakim (Emerald Group Publishing, 2021)
Purpose: This paper aims to examine the effect of e-evaluation on work motivation among teachers during the Movement Control Order (MCO) in COVID-19 and determining the mediating role of stress. Design/methodology/approach: The study is designed using a causal research design to examine the cause-effect relationship between the study variables. The study sample consists of 595 school teachers selected via convenient sampling. Quantitative data are collected from an online survey through the questionnaires with demographic, stress, e-evaluation and work motivation developed by the researchers were distributed during the MCO period. To test the model, structural equation modelling (SEM) was applied by using AMOS 21. Findings: The results indicated that the e-evaluation, stress and work motivation of teachers during the MCO were conducted at a moderate level. The stress relationship with work motivation of teachers was also weak and showed a negative relationship, while e-evaluation and work motivation showed a strong relationship. The results of the SEM analysis revealed that the model fit was achieved with RMSEA = 0.07, GFI = 0.96, CFI = 0.98, TLI = 0.97, ChiSq/df = 4.30 and p = 0.00. In addition, there was no role of stress as a mediator in the relationship between e-evaluation and work motivation and e-evaluation contributed 54% to work motivation. Research limitations/implications: This study underlines our contention that teachers’ work motivation correlated positively with their e-evaluation. The findings suggest that teachers’ stress cannot mediate the relationship between e-evaluation and work motivation. The limitations of the study include the convenience sampling, non-probability sampling technique, not chosen at random and undermines the generalizations from sample to the population. Practical implications: The results provide a useful framework to teachers for the successful implementation of e-evaluations in their instruction to enhance their work-motivation. Originality/value: There is a lack of e-evaluation studies in teacher education and teaching strategies, and the correlation between e-evaluation and work motivation during COVID-19 pandemic is often absent.